Production of a sensitive antibody against sirolimus for chemiluminescence immunoassay potential in its therapeutic drug monitoring. Issue 33 (4th August 2016) - Zhang, Lisha; Long, Hao; Li, Xiaogang; Xu, Kun; Meng, Meng; Yin, Yongmei; Xi, Rimo
Abstract : A competitive chemiluminescence immunoassay is established and applied to the TDM of sirolimus. Abstract : In this study, a specific antibody against sirolimus was produced by its well synthesized immunogen and a competitive chemiluminescence immunoassay (CLIA) was established. The sirolimus molecule was modified with succinic anhydride (hapten 1) and carboxymethoxylamine (hapten 2). Hapten 1 was conjugated with bovine serum albumin to serve as the immunogen whilst hapten 2 was conjugated with ovalbumin for the coating antigen. A polyclonal antibody was prepared by immunizing rabbits with the purified immunogen. A CLIA method was established using the antibody for the analysis of sirolimus in phosphate-buffered saline and plasma. The limits of detection of the method in the two samples could reach 0.20 and 0.25 ng mL −1, respectively. Furthermore, this immunoassay was successfully applied to the pharmacokinetic study of sirolimus and the calculation of its pharmacokinetic parameters. The results suggest that this immunoassay has significant potential to be developed as a kit which can provide a sensitive, specific and inexpensive approach to therapeutic drug monitoring of sirolimus.